Comparison of Indonesian and Malaysian Investment Laws Following Omnibus Legislation - Sudiyana Sudiyana; Mohd Zamre Mohd Zahir (Faculty of Law, Universitas Sebelas Maret, 2025)
Government initiatives like the Omnibus Law encourage investment and job creation. This article examines and evaluates the investment law policy following the Omnibus Law on Job Creation compared to Malaysian legislation. This normative legal research examines challenges using progressive legal theory and statutory and conceptual approaches. According to the Omnibus Law Job Creation, the investment law policy starts with legality in risk-based business, offers investment incentives to boost foreign investment, and expands business opportunities while upholding national interest. Employment creation is more progressive under this post-omnibus law. Investment policies harmonize legislation and investment institution coordination. Indonesia has more centralized laws than Malaysia. Malaysia's legal investment policy is sectoral. Each business sector must have a supervisory entity, and all investments must register as Malaysian businesses.